PENGARUH PENAMBAHAN KALIUM HIDROKSIDA (KOH) TERHADAP MUTU SABUN LUNAK BERBAHAN DASAR MINYAK GORENG BEKAS - Maria Mita Susanti; Alicia Dinta Assuncao Guterres (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2018)
The increasing of pollution, dirt, sweat and bacteria on skin surface, make the need for soap increase. One form of soap is soft soap, which made from potassium salt with fatty acids. The oil phase that can be used is cooking oil with a frequency of three times frying. The purpose of this study is to determine the effect of addition of potassium hydroxide on the quality characteristics of soft soap produced. This type of research is an experimental study with a complete randomized design study of one factor on the addition of potassium hydroxide (13 g, 15 g and 17 g). Quality characteristics tests include organoleptic, pH, foam power, moisture content, free alkali and free fatty acids. Data were analyzed theoretically and statistically using Shapiro-Wilk for data normality, and Levene Statistic for data homogeneity. Normal and homogeneous data were followed by Anova test, and normal but not homogeneous data followed by Kruskal-Wallis test. Based on the results of the characteristic test showed that formula II met the quality characteristics test of soft soap, with a pH value of 10, foam power 2,26-2,30 cm, moisture content 44%, free alkali 0,08%, and free fatty acids 1,42%. Formula I does not meet the foam power test (2,20 cm) which is 2,03-2,06 cm, while the formula III does not meet the pH test requirements (7-10) that is 11. Based on the results of the data analysis the three formulas show the value (p<0,05) means that the addition of potassium hydroxide affects the quality characteristics of soft soap.